How Narcissistic Leaders Impact on Subordinate’s Followership During the COVID-19? The Moderating Role of Organizational Identification - Wang, Lin; Guo, Qun (Frontiers in Psychology, 2022)
The COVID-19 pandemic gave rise to social and economic problems and pose a threat to most of enterprise. Faced with crisis and challenge, effective leaders and devoted employees are important factors for enterprises to overcome difficulties. We propose a moderated mediation model wherein narcissistic leader predicts subordinate’s followership through leader self-interest behavior perceived by subordinates, with organizational identification of leader acting as the contextual condition. Two-wave data collected from 303 employees in the manufacturing and technology industry in China supported our hypothesized model. We found that narcissistic leader has negative impact on subordinates’ followership due to their perception of leader’s self-interest behavior. Further, organizational identification of leader plays a moderate role in the relationship between narcissistic leader and subordinates’ followership. Theoretical and practical implications are discussed. We also offer several promising directions for future research.